Implementation of Business Process Reengineering for Efficiency of Raw Material Procurement and Inventory Management at CV Jaya Mitra Chemical - Adinda Nabila Firnanda; Ghea Sekar Palupi (Universitas Negeri Surabaya, 2026)
CV. Jaya Mitra Chemical is a company engaged in the sale and purchase of chemical products, providing chemicals (chemical maintenance) for industry, shipping, shipbuilding, and offshore oil drilling. The main problem faced is closely related to the length of the cycle time in the business process, particularly in the procurement and management of chemical raw material supplies. This research was conducted to implement Business Process Reengineering at CV Jaya Mitra Chemical to optimize the company's cycle time efficiency by identifying and correcting weaknesses in the business processes of procurement and management of raw material supplies and to determine the percentage increase in the company's cycle time efficiency resulting from the implementation of Business Process Reengineering in the procurement and management of raw material supplies at CV. Jaya Mitra Chemical. The business process reengineering (BPR) process was assisted by BPMN, value-added analysis, and root cause analysis (fishbone diagram), followed by To-Be modelling using a heuristic redesign approach. After implementing BPR in the procurement and management of raw material inventory (using the CV Delivery Section as the collection method), the average business process cycle time decreased from 3 hours 11 minutes 37 seconds to 1 hour 56 minutes 7 seconds, which means that efficiency increased by 39.4% CTE. There was a reduction in time of 1 hour 15 minutes 30 seconds. Then, in the Procurement and Management of Raw Material Inventory Process (using Gosend courier services), the average business process cycle time decreased from 3 hours 9 minutes 11 seconds to 2 hours 18 minutes 42 seconds, which means efficiency increased by 26.7% CTE and experienced a time reduction of 50 minutes 29 seconds.